Disillusioned Victorian photography and the discerning subject - Bear, Jordan (The Pennsylvania State University Press, 2015)
"Examines how photographic trickery in the 1850s and 1860s participated in the fashioning of the modern subject. Integrates images of the Victorian period into a new and expansive interpretive framework by locating specific mechanisms of photographic deception"--Provided by publisher.